2011
DOI: 10.1111/j.1365-3024.2011.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus granulosus glycoconjugates induce peritoneal B cell differentiation into antibody‐secreting cells and cytokine production

Abstract: Helminth parasite infections are associated with predominant Th2-type cytokine responses, and parasite glycoconjugates have been recognized as partially responsible for such immune bias. It has been proved that Echinococcus granulosus evokes a Th2-type cytokine pattern characterized by a high production of IL-4, IL-5, IL-6 and IL-10, and no or mild IFN-γ levels in animal models and in patients with cystic echinococcosis, respectively. Here, we show that E4(+) (a glycoconjugate-enriched fraction from E. granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 92 publications
(113 reference statements)
2
14
0
Order By: Relevance
“…A previous study found that a glycoconugate-enriched fraction from EgPSC stimulated the secretion of IL-10 production by peritoneal B cells [25]. However, whether this process is directly triggered by ESPs remains to be established.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study found that a glycoconugate-enriched fraction from EgPSC stimulated the secretion of IL-10 production by peritoneal B cells [25]. However, whether this process is directly triggered by ESPs remains to be established.…”
Section: Resultsmentioning
confidence: 99%
“…PSC carbohydrate fractions are immunodominant in both mice and humans and are mainly recognized by IgG4 in humans, an isotype with poor ability to induce complement and cell activation . PSC carbohydrate fractions (E4 + ) have also been shown to induce IL‐10 and to reduce splenocyte proliferation in vitro . Moreover, PSC present Fc‐binding activity, which could interfere with effector functions of human IgG1 and IgG3 (Figure b).…”
Section: Immune Response In the Intermediate Hostmentioning
confidence: 99%
“…Increased Th1 responses (IFNγ or IL-12) impair PSC survival and cyst development, while IL-4 and IL-10 induce heavier cyst loads and impair PSC killing (Al-Qaoud and Abdel-Hafez 2008; Amri et al 2007Amri et al , 2009). Other mechanisms of immune evasion include polyclonal activation of B cells (Cox et al 1989) and induction of IL-10, IgG4, and high levels of nonspecific antibodies and lack of antibody avidity maturation, as shown experimentally by injection of carbohydrate fractions of PSC (Miguez et al 1996;Mourglia-Ettlin et al 2011a;Ferragut and Nieto 1996;Severi et al 1997;Baz et al 1999Baz et al , 2008Cardozo et al 2002;Dematteis et al 2001). Moreover, PSC present Fc-binding activity (Baz et al 1998) and express immune regulatory antigen B and EgTeg (Ortona et al 2005;Sanchez et al 1991;Monteiro et al 2010).…”
Section: Immune Response To E Granulosusmentioning
confidence: 95%